2012
DOI: 10.1021/la3000944
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Gold Nanorods Passivated with Amphiphilic Ligands

Abstract: The stability of gold nanorods (NRs) coated with amphiphilic ligands (ALs) was investigated. NRs coated with cetyltrimethylammonium bromide (CTAB) were ligand exchanged with polyoxyethylene [10] cetyl ether (Brij56), Oligofectamine (OF), and phosphatidylserine (PS). An aggregation index based on the longitudinal surface plasmon resonance peak broadening was used to measure stability of the NR-ALs under different conditions including the number of washes, pH, ionic concentration, and temperature. The aggregatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
78
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(81 citation statements)
references
References 44 publications
3
78
0
Order By: Relevance
“…This is due to the fact that NP properties are strongly dependent on their surrounding environment [30,31]. DLS analysis indicated that the particles did agglomerated in SF media, with an approximate hydrodynamic diameter of 150 nm.…”
Section: Characterization and Dosage Selection Of Agnpsmentioning
confidence: 99%
“…This is due to the fact that NP properties are strongly dependent on their surrounding environment [30,31]. DLS analysis indicated that the particles did agglomerated in SF media, with an approximate hydrodynamic diameter of 150 nm.…”
Section: Characterization and Dosage Selection Of Agnpsmentioning
confidence: 99%
“…Theoretical models have linked AR dependent spectral signatures of Au-NRs to projected photothermal efficiencies and have identified particle absorbance to be the predominant factor contributing to the nanophotonic response [11]. Furthermore, previous studies have shown that ionic strength and refractive index of the dispersant fluid directly impacts the absorbance, agglomeration state, and stability of Au-NRs: all of which have the potential to modify the innate photothermal abilities of these nano-sized particles [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Aggregation of particles has been shown to have wide-reaching effects and influences outcomes including cytotoxicity, rate of internalization, particle distribution, and spectral profiles [12]. Agglomeration induced modifications to a nanomaterial's absorption spectrum would cause a significant change in nanophotonic response as absorbance is the dominant physical basis for photothermal therapy and imaging applications [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the interplay between the 226 electrostatic interaction of molecules surrounding the NRs with the positively charged CTAB bilayer 227 and the destabilization of the CTAB bilayer induced by the PBS at physiological pH, amino acid 228 residues of the protein get in close contact with NRs gold surface [63,64,65,66]. This yields the 229 formation of biomolecule-NRs complexes [65,67] in which individual NRs are stabilized by the 230 protein layer in the solution.…”
mentioning
confidence: 99%
“…This is also the case of NRs 238 covered with CTAB. When we mix BSA (10 -4 M) in PBS (200 mM in water), the high ionic 239 concentration and the pH value of 7.2 causes the destabilization of the CTAB bilayer surrounding 240 the NRs [63]. The presence of BSA and its fast interaction with the gold surface (they form a stable 241 bound in less than 1 µs [65]) ensures a new protein capping layer that can stabilize the suspension.…”
mentioning
confidence: 99%